2018
DOI: 10.1002/ajmg.a.40502
|View full text |Cite
|
Sign up to set email alerts
|

Silver Russel syndrome in an aboriginal patient from Australia

Abstract: Silver-Russell syndrome (SRS OMIM 180860) is a rare, albeit well-recognized disorder characterized by severe intrauterine and postnatal growth retardation. It remains a clinical diagnosis with a molecular cause identifiable in approximately 60%-70% of patients. We report a 4-year-old Australian Aboriginal girl who was born at 32 weeks gestation with features strongly suggestive of SRS, after extensive investigation she was referred to our undiagnosed disease program (UDP). Genomic sequencing was performed whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…Body asymmetry, a frequent characteristic in SRS caused by mosaic IC1 hypomethylation, was absent in the index patient and his affected mother. This is in agreement with the previous clinical findings in patients with the p.Arg279Leu variant [4,5], the sporadic case from Japan [6] and other patients with SRS and genomic mutations of IGF2 which were not mosaic [20][21][22][23][24]. In agreement with a previous report [5], IGF-1 serum levels were normal in the index patient and his mother.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Body asymmetry, a frequent characteristic in SRS caused by mosaic IC1 hypomethylation, was absent in the index patient and his affected mother. This is in agreement with the previous clinical findings in patients with the p.Arg279Leu variant [4,5], the sporadic case from Japan [6] and other patients with SRS and genomic mutations of IGF2 which were not mosaic [20][21][22][23][24]. In agreement with a previous report [5], IGF-1 serum levels were normal in the index patient and his mother.…”
Section: Discussionsupporting
confidence: 93%
“…Since the first report of a genomic IGF2 mutation in familial SRS by Begemann et al [12], eleven additional IGF2 mutations in only sporadic cases were reported [13,[20][21][22][23][24]. This number is not high, but higher than the three families and one sporadic case reported with genomic CDKN1C mutations and SRS ( [4][5][6], this study).…”
Section: Discussionmentioning
confidence: 49%
“…A maternal CDKN1C gain-of-function variant has been reported as a rare cause of SRS (Eggermann et al, 2014). Recently, five reports have identified IGF2 loss-of-function variants as new contributors to the molecular etiology of SRS, on the basis of studies including individuals of German, Japanese, Chinese, and Australian Aboriginal descent ( Table 1 ) (Begemann et al, 2015; Liu et al, 2017; Yamoto et al, 2017; Abi Habib et al, 2018; Poulton et al, 2018). In our SRS patient from China, we found a novel IGF2 splicing variant, NM_000612.4: c.157+5G > A, which is located on the paternal allele.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, five reports revealed SRS-associated IGF2 variants. However, the variants and phenotypic spectrum remain very limited (Liu et al, 2017; Yamoto et al, 2017; Abi Habib et al, 2018; Poulton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Through exome analysis, the authors identified an IGF2 nonsense mutation in all patients, inherited from their healthy fathers (OMIM 616489) (51). After this first report, other five studies identified variants in IGF2 gene on the paternal allele causing SRS-like (52)(53)(54)(55)(56). Up to now, one missense and six loss-of-function variants (3 frameshift, 2 nonsense and 1 splice-site) in the IGF2 gene were reported.…”
Section: Igf2 Defectsmentioning
confidence: 98%